Political Wilayah between Divine Investiture and Human Election: A Comparative Study - Zaki Yahya, Mustafa; Zaki Yahya, Mustafa ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
This study seeks to ascertain the possibility of deriving, through juristic analysis, the Sunni fiqh perspective on political wilayah-its locus and the party entitled to its conferral-and to assess the extent of its coherence with the theoretical premises of Imami jurisprudence concerning the nature of the political authority vested in the jurist (al-faqih). The inquiry therefore concentrates on the foundational bases, legitimacy, and qualifications of the ruler, posing the question: Does Sunni fiqh articulate a juristic conception of the Islamic ruler comparable to that formulated in Imami legal thought? Employing a comparative method in examining the evidentiary texts and analyzing the doctrinal underpinnings of both traditions, the study concludes that wilayah in Imami jurisprudence rests upon divine designation (al-nasb al-ilahi) and delegated authority (al-niyabah), whereas in Sunni legal theory it is grounded in consultation (al-shura) and the pledge of allegiance (al-bay’ah). In Imami doctrine, knowledge, justice, and ijtihad constitute conditions of validity (shurut al-sihhah), while in the majority of Sunni schools they are regarded as conditions of perfection (shurut al-kamal). Hence, the Imamiyyah stipulate juristic qualification as a requirement for rulership, whereas most Sunnis do not, although certain leading Sunni authorities have advanced positions approximating the substance of wilayah, albeit under a different designation. DOI: https://doi.org/10.54633/2333-024-057-014